Postmodern belief : American literature and religion since 1960 - Hungerford, Amy (20/21 (Princeton, N.J.), 2010)
How can intense religious beliefs coexist with pluralism in America today? Examining the role of the religious imagination in contemporary religious practice and in some of the best-known works of American literature from the past fifty years, Postmodern Belief shows how belief for its own sake--a belief absent of doctrine--has become an answer to pluralism in a secular age. Amy Hungerford reveals how imaginative literature and religious practices together allow novelists, poets, and critics to express the formal elements of language in transcendent terms, conferring upon words a religious val.